2015
DOI: 10.4314/sajas.v45i4.6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of niacin supplementation (40 weeks) and two dietary levels of concentrate on performance, blood and fatty acid profiles of dairy cattle

Abstract: The present study was conducted to investigate the effects of 24 g niacin (nicotinic acid (NA)) supplementation over 40 weeks with two forage-to-concentrate ratios (60% concentrate vs. 30% in the total diet) on performance variables of energy metabolism such as plasma concentrations of non-esterified fatty acids (NEFA), beta-hydroxybutyrate (BHB), glucose and nicotinamide (NAM), and the fatty acid profile in rumen fluid. In a 2 x 2 factorial design, 64 German Holstein cows were divided postpartum into four die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…A positive relationship between C and milk yield would have been expected due to the additionally provided energy in the diet as had been proved in previous studies [12,26,40]. BCS had no influence on milk yield either.…”
Section: Discussionsupporting
confidence: 64%
“…A positive relationship between C and milk yield would have been expected due to the additionally provided energy in the diet as had been proved in previous studies [12,26,40]. BCS had no influence on milk yield either.…”
Section: Discussionsupporting
confidence: 64%
“…Milk yield and body weight after milking were recorded automatically (Lemmer Fullwood GmbH, Lohmer, Germany) daily. The actual intake of NA was 1.0 ± 0.0, 2.8 ± 0.03, 20.5 ± 0.2, and 21.0 ± 0.3 g/d for CON-LC, CON-HC, NA-LC, and NA-HC, respectively [ 9 ]. Nutrient, energy and fiber contents of the silages and concentrate as well as the composition of the diet fed to each experimental group post partum are presented as supporting information ( S1 Table ).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, a trial was conducted to assess—besides anti-lipolytic action—potential effects of NA on hepatic and adipose insulin signaling and glucose transporter expression. Primiparous and pluriparous cows were fed diets with two different concentrate proportions with or without NA supplementation over the entire lactation period [ 9 ]. Of these, a subset of cows that were randomly selected and were used for the present study.…”
Section: Introductionmentioning
confidence: 99%
“…We had, therefore, administered additional vitamin B‐complex and choline along with glycerol and anti‐oxidants in anticipation that their supplementation would result in better tissue utilization of glucose and drop in blood glucose and cortisol concentration. More recently it has been found that niacin administration to cows during the post‐partum period significantly reduced blood glucose level, decreased lipolysis in adipose tissue and concentration of circulating non‐esterified fatty acid (NEFA) and increase milk production (Rauls et al, 2015). Other studies have found that supplementation of cows at post‐partum period with additional B‐ complex vitamins with choline significantly increased the fat % and protein % in milk (Evans et al, 2006).…”
Section: Discussionmentioning
confidence: 99%